2015
DOI: 10.5603/kp.a2015.0038
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural checklist in the catheterisation laboratory is associated with decreased rate of treatment complications

Abstract: Introduction of a periprocedural checklist was associated with significant reduction of adverse events among patients undergoing invasive procedures. It also showed a positive influence on team communication, and organisation and quality of treatment, according to the opinions of medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Use of on-site developed checklists were reported to reduce complications [115][116][117] , mortality 118 and unplanned readmissions 86 . Nevertheless, there were also such studies reporting no change in complications 90,119 or mortality 90 .…”
Section: Re-admission Los Othersmentioning
confidence: 99%
“…Use of on-site developed checklists were reported to reduce complications [115][116][117] , mortality 118 and unplanned readmissions 86 . Nevertheless, there were also such studies reporting no change in complications 90,119 or mortality 90 .…”
Section: Re-admission Los Othersmentioning
confidence: 99%
“…In other countries, although still with few publications, the use of a checklist for interventional Radiology has been positive ( 21 - 22 ) . It provides staff with communication support, assisting in safe patient care ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a study conducted in Poland analyzed the effect of the checklist in the decrease of adverse events in 2,064 invasive Cardiological and electrophysiological procedures. The use of a checklist was associated with a significant reduction of adverse events, especially bleeding, a decrease in the number of errors related to health care, and positive contribution in the organization and communication within the team ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the potential complications are common, such as perforation of heart chamber with bleeding and pericardial tamponade, or embolic stroke from when insufficient anticoagulation. Previous studies have reported that the introduction of periprocedural checklists in the electrophysiology and cardiac catheterization suites has improved communications skills, work organization and reduced the occurrence of these errors and complications [16]. At our institution, we have established ‘mini-checklists’ for procedures, such as catheter ablations.…”
Section: Electrophysiology and Cardiac Catheterization Laboratorymentioning
confidence: 99%